2008
DOI: 10.1016/j.rmed.2008.04.015
|View full text |Cite
|
Sign up to set email alerts
|

Educational impact of pulmonary rehabilitation: Lung Information Needs Questionnaire

Abstract: This study shows that the LINQ is a practical tool for detecting areas where patients need education and is sensitive to change after PR. The quality of the education component of PR can be assessed using the LINQ, which could be considered as a routinely collected outcome measure in PR. The LINQ may also be a useful tool for general practitioners to assess their patients' educational needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
46
1
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(61 citation statements)
references
References 13 publications
(15 reference statements)
9
46
1
5
Order By: Relevance
“…Inviting a former pulmonary rehabilitation graduate or member of a local Breathe Easy group should be considered. Supplementing the talks with written educational information is advised. Patient satisfaction surveys and questionnaires containing disease-specific information (eg, for the Lung Information Needs Questionnaire or the Bristol Chronic Obstructive Pulmonary Disease Knowledge questionnaire) ensure quality of the educational aspects 210 211

Supplemental practical information is provided by the service specification for pulmonary rehabilitation at http://www.dh.gov.uk/health/2012/08/copd-toolkit/209

…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inviting a former pulmonary rehabilitation graduate or member of a local Breathe Easy group should be considered. Supplementing the talks with written educational information is advised. Patient satisfaction surveys and questionnaires containing disease-specific information (eg, for the Lung Information Needs Questionnaire or the Bristol Chronic Obstructive Pulmonary Disease Knowledge questionnaire) ensure quality of the educational aspects 210 211

Supplemental practical information is provided by the service specification for pulmonary rehabilitation at http://www.dh.gov.uk/health/2012/08/copd-toolkit/209

…”
Section: Introductionmentioning
confidence: 99%
“…Patient satisfaction surveys and questionnaires containing disease-specific information (eg, for the Lung Information Needs Questionnaire or the Bristol Chronic Obstructive Pulmonary Disease Knowledge questionnaire) ensure quality of the educational aspects 210 211…”
Section: Introductionmentioning
confidence: 99%
“…10 However, their results cannot be directly compared to ours because their patient population had less severe COPD and the researchers did not investigate specific knowledge regarding COPD. Jones et al, 11 using a questionnaire to test the educational impact of pulmonary rehabilitation, in a study with a similar design to ours, concluded that "a structured educational track may help to rectify patients' gap of knowledge on the management of their respiratory condition." 11 Our results are also consistent with findings from Crisafulli et al, 12 who described a program in a rehabilitation setting similar to ours.…”
Section: Discussionmentioning
confidence: 64%
“…Jones et al, 11 using a questionnaire to test the educational impact of pulmonary rehabilitation, in a study with a similar design to ours, concluded that "a structured educational track may help to rectify patients' gap of knowledge on the management of their respiratory condition." 11 Our results are also consistent with findings from Crisafulli et al, 12 who described a program in a rehabilitation setting similar to ours. Indeed, they found a high attendance rate (79%) to the program, demonstrating the acceptability and perceived worth of educational programming in a COPD population.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation